Markers of bone remodeling in metastatic bone disease - Fohr, Berthold; Dunstan, Colin R.; Seibel, Markus J. (The journal of clinical endocrinology & metabolism, 2003)
Many cancers have a strong propensity to spread to bone. The processes involved in cancer dissemination to bone are complex and variable, and the changes in bone metabolism, once bony metastases have occurred, are usually profound. This review surveys the usefulness of bone markers in the diagnosis and follow-up of patients with malignant bone disease.In patients with established bone metastases, most markers of bone remodeling are abnormal compared with healthy controls or cancer patients without bone lesions. Although bone markers may have a potential as diagnostic tools in cancer patients, the available data do not allow final conclusions regarding the accuracy and validity of any of the presently used markers in the diagnosis of bone metastases.As regards monitoring of anticancer therapy, most markers of bone remodeling respond to active treatments. These indices therefore may have the potential to be used in the monitoring of antitumor therapies. However, most if not all of the available evidence on the use of bone markers in monitoring anticancer therapy is observational, and it remains unclear whether they have any beneficial effects on overall outcome. The same is true for their prognostic value, although evidence suggests that suppressed levels of bone formation or high rates of bone resorption are independent predictors of poor survival.
Gesehen am 30.06.2022